Exhibiting photography a practical guide to displaying your work - Read, Shirley (Focal Press, 2014)
You have the camera, you have the skills, and you have the pictures. Now what? Author Shirley Read expertly leads you through the world of exhibiting your photography one minute detail at a time. From finding a space and designing the exhibition to actually constructing a show and publicizing yourself, every aspect of exhibiting your photography is touched upon and clarified with ample detail, anecdotes, and real life case studies. In this new and expanded second edition, Shirley Read further illuminates the world of social networking, exhibiting, and selling photography online so your work.